Thermal expansion microspheres with smooth surface and preparation method thereof

Through nanolignin stabilizer and high-speed homogeneous emulsification technology, combined with alkali washing, the problem of thermal expansion microspheres in the prior art is not suitable for acidic or alkaline environments, and a smooth surface thermal expansion microspheres are prepared, which improves their Application areas and performance.

CN118852724BActive Publication Date: 2025-01-03YINGXING NEW MATERIALS (YANTAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411321170.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing thermally expanded microspheres are not suitable in acidic or alkaline environments, and the suspension polymerization process is difficult to prepare thermally expanded microspheres with smooth surfaces, which limits their application areas.

Method used

Nanolignin is used as the emulsion stabilizer, and the surface of the thermally expanded microspheres are prepared by mixing unsaturated olefin monomers, crosslinking agents, initiators and foaming agents, combined with high-speed homogeneous emulsification and alkaline washing technology.

Benefits of technology

The surface smooth thermal expansion microspheres are obtained for acidic or alkaline environments, which improve the expansion ratio and airtightness, and are suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852724B_ABST
    Figure CN118852724B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer functional materials, in particular to heat-expandable microspheres with smooth surfaces and a preparation method thereof, comprising the following steps: S1: mixing unsaturated olefin monomers, a crosslinking agent, a modifier, an initiator and a foaming agent, stirring evenly to form a mixed oil phase; S2: mixing nano-lignin aqueous dispersion, an emulsifier and a water phase inhibitor evenly, stirring evenly to form a mixed water phase; S3: adding the mixed water phase obtained in step S2 to the mixed oil phase obtained in step S1, homogenizing and emulsifying at high speed to form an emulsion; S4: adding the emulsion obtained in step S3 to a reactor, sealing, pressurizing, stirring and heating to react, to obtain a heat-expandable microsphere suspension; and S5: adding an alkali washing solution to the heat-expandable microsphere suspension obtained in step S4 to dissolve the nano-lignin on the surface of the heat-expandable microspheres, filtering, alkali washing and drying in sequence to finally obtain heat-expandable microsphere powder with smooth surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer functional materials, and in particular to thermal expansion microspheres with smooth surfaces and a preparation method thereof. Background Art

[0002] Heat-expandable microspheres are micron-sized particle microspheres with a core-shell structure formed by coating a foaming agent with a polymer. When the heat-expandable microspheres are heated, the polymer shell softens, and the foaming agent begins to vaporize and generate air pressure, causing the microspheres to expand by dozens or hundreds of times. Heat-expandable microspheres have been widely used in leather clothing, sole materials, clay toys, cosmetics, electronic devices, and automotive materials. The polymer shell material of such heat-expandable microspheres usually uses vinylidene chloride copolymers, acrylonitrile copolymers, and acrylate copolymers, while the foaming agent mainly uses low-chain alkanes such as isobutane, isopentane, and isooctane. In the process of preparing heat-expandable microspheres, in addition to the polymer shell material and the foaming agent, the emulsification system used is also particularly important. The emulsification system directly affects the surface physical and chemical properties of the heat-expandable microspheres, limiting their application areas.

[0003] At present, the preparation of heat-expandable microspheres uses a suspension polymerization process, and the emulsification systems used are mainly magnesium hydroxide emulsification systems and silicon dioxide emulsification systems. Using the magnesium hydroxide system, the overall emulsification and reaction system is alkaline, and finally alkaline heat-expandable microspheres are obtained. Magnesium hydroxide particles will adhere to the surface, and after mixing with the matrix resin, it will affect the viscosity and rheological properties, limiting its application conditions. It is necessary to use acid to clean it to obtain heat-expandable microspheres with smooth surfaces. Although it can improve its application conditions, it is still not suitable for acidic or alkali-sensitive application environments. Using the silicon dioxide emulsification system, silicon dioxide is acidic to maintain stable dispersion in water, and silicon dioxide is difficult to remove using acid-base reagents and organic solvents. Finally, the acidic heat-expandable microspheres with unsmooth surface adsorbed silica sol particles are obtained, and they are not suitable for alkaline or acid-sensitive application environments. Therefore, considering the diversity of application fields of heat-expandable microspheres, it is urgent to develop a new type of heat-expandable microspheres with smooth surface and no particle adhesion in the heat-expandable microsphere product system.

[0004] The Chinese invention patent application with publication number CN118179596A discloses a lignin porous microsphere loaded with metal nanoparticles and a preparation method and application thereof, comprising the following steps: uniformly mixing a lignin alkaline solution, a crosslinking agent and a chain extender to obtain a lignin aqueous solution; mixing the lignin aqueous solution and an inner oil phase containing a surfactant, emulsifying, to obtain an O / W type colostrum; then mixing the O / W type colostrum and an outer oil phase containing a surfactant, emulsifying, to obtain an O / W / O type multiple emulsion; subjecting the O / W / O type multiple emulsion to ultrasonic reaction, removing the oil phase after the reaction is terminated, washing, to obtain lignin porous microspheres; suspending and dispersing the lignin porous microspheres in an aqueous solution of a metal salt, heating or ultrasonic reaction, separating and drying, to obtain lignin porous microspheres loaded with metal nanoparticles. The above scheme utilizes lignin to generate lignin porous microspheres, and utilizes the adsorption of the lignin porous microspheres to load the metal nanoparticles on the lignin porous microspheres, but the above disclosed scheme does not disclose a technical scheme for generating surface-smooth thermal expansion microspheres using lignin. Summary of the invention

[0005] Technical purpose: In order to overcome the deficiencies in the prior art, the present invention provides thermal expansion microspheres with smooth surface and a preparation method thereof.

[0006] Technical solution: To achieve the above purpose, the method for preparing thermally expandable microspheres with smooth surface disclosed in the present invention comprises the following steps:

[0007] S1: Mix unsaturated olefin monomer, crosslinking agent, modifier, initiator and foaming agent, stir evenly to form a mixed oil phase;

[0008] S2: uniformly mix the nano-lignin aqueous dispersion, the emulsifier and the water phase inhibitor, and stir to form a mixed water phase;

[0009] S3: adding the mixed water phase obtained in step S2 to the mixed oil phase obtained in step S1, and homogenizing and emulsifying at high speed to form an emulsion;

[0010] S4: adding the emulsion obtained in step S3 into a reaction kettle, sealing, pressurizing, stirring, and heating for reaction to obtain a heat-expandable microsphere suspension;

[0011] S5: adding alkaline washing liquid to the heat-expandable microsphere suspension obtained in step S4 to dissolve the nano-lignin on the surface of the heat-expandable microspheres, filtering, alkali washing and drying in sequence, and finally obtaining heat-expandable microsphere powder with a smooth surface.

[0012] Preferably, the unsaturated olefin monomer accounts for 67-80wt% of the total oil phase; the unsaturated olefin monomer includes monofunctional acrylate, and the monofunctional acrylate is one or more of acrylonitrile, methacrylonitrile, methyl methacrylate, ethyl methacrylate, methyl acrylate, butyl acrylate, n-butyl methacrylate, amyl methacrylate, isopentyl methacrylate, cyclohexyl acrylate, n-heptyl acrylate, 2-ethylhexyl acrylate, n-nonyl methacrylate, and isononyl acrylate.

[0013] Preferably, the cross-linking agent is used in an amount of 0.1 to 1.0 wt % of the total oil phase; the cross-linking agent comprises a multifunctional acrylate, and the multifunctional acrylate is one or more of ethylene glycol dimethacrylate, ethylene glycol diacrylate, dipropylene glycol dimethacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, polyethylene glycol dimethacrylate, and polypropylene glycol dimethacrylate.

[0014] Preferably, the modifier is used in an amount of 0 to 1.0 wt % of the total oil phase; the modifier includes a compound containing a carbon-carbon double bond, and the compound containing a carbon-carbon double bond is one or a combination of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, isobornyl acrylate, isobornyl methacrylate, vinylsilane trimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmonomethoxysilane, vinylsilane triethoxysilane, vinylmethyldiethoxysilane, and vinyldimethylmonoethoxysilane.

[0015] Preferably, the initiator is used in an amount of 0 to 1.0 wt % of the total oil phase, and the initiator is one or more of toluoyl peroxide, lauroyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, azobisisobutyronitrile, azobisisoheptylnitrile, azoisobutylcyanamide, di-sec-butyl peroxydicarbonate, and dibenzyl peroxydicarbonate.

[0016] Preferably, the foaming agent is used in an amount of 20-30wt% of the total oil phase; the foaming agent is one or more of n-butane, isobutane, n-pentane, isopentane, neopentane, cyclopentane, hexane, isohexane, octhexane, cyclohexane, heptane, isoheptane, octane and isooctane.

[0017] Preferably, the nano-lignin aqueous dispersion accounts for 90-100wt% of the total aqueous phase; the nano-lignin aqueous dispersion is a nanoparticle aqueous dispersion prepared from water-insoluble lignin, the water-insoluble lignin is nano-alkali lignin, enzymatic lignin or sulfonate lignin, the nano-alkali lignin has a solid content range of 0.6-1.2wt%, and a particle size range of 10-500nm.

[0018] Preferably, the amount of the co-emulsifier accounts for 0 to 0.2 wt% of the total aqueous phase; the co-emulsifier is one or more of sodium dodecyl sulfate, ammonium dodecylbenzenesulfonate, alkyl dimethyl sulfoethyl betaine, alkyl dimethyl sulfopropyl betaine, alkyl dimethyl hydroxypropyl phosphate betaine, polyvinyl alcohol, polyvinyl pyrrolidone, sodium alginate, gelatin, and methyl cellulose; the amount of the water phase inhibitor accounts for 0 to 0.05 wt% of the total aqueous phase; the water phase inhibitor is one or more of sodium nitrite, ferric nitrate, chromium nitrate, dichromate, tin chloride, ferric chloride, water-soluble ascorbic acid and its derivatives.

[0019] Preferably, the high-speed homogenization and emulsification speed in step S3 is 6000-14000 rpm, the specific parameters of the sealing pressurization, stirring and heating reaction in step S4 are: pressure of 0.4-0.6 MPa, stirring speed of 60-150 rpm, reaction temperature of 50-60° C., and insulation reaction time of 15-20 h, and the alkaline washing solution in step S5 is a sodium hydroxide aqueous solution with a concentration of 1-4 mol / L, or a potassium hydroxide aqueous solution with a concentration of 1-4 mol / L, or a mixed solution of sodium hydroxide and potassium hydroxide with a concentration of 1-4 mol / L.

[0020] The present invention also provides thermal expansion microspheres with smooth surface, which are obtained by any of the above preparation methods.

[0021] The beneficial effects of the present invention are:

[0022] Lignin is a natural polymer second only to cellulose in content in the plant kingdom. It is very easy to obtain and inexpensive. It has an amphiphilic structure and can be processed into nanoparticles to be a good emulsion stabilizer. In addition, lignin has the characteristics of precipitating in acidic water and dissolving in alkaline aqueous solution. The method uses nano-lignin as an emulsion stabilizer, emulsifies the oil phase, and uses a suspension polymerization method to prepare heat-expandable microspheres. After alkali washing, filtering, and drying, heat-expandable microspheres with a smooth surface and no particles are obtained for subsequent processing and application. In addition, the heat-expandable microspheres with a smooth and clean surface will not be affected by the uneven stress caused by the physical action of the physical particles on the surface during the expansion process, and have a higher expansion ratio and better air tightness. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope (SEM) image of the heat-expanded microspheres obtained in Example 1 of the present invention;

[0024] Figure 2 This is a scanning electron microscope (SEM) image of the heat-expanded microspheres obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The following is combined with Figure 1 To Attachment Figure 2 The principles and features of the present invention are described, and the examples given are only used to explain the present invention, not to limit the scope of the present invention.

[0026] The method for preparing thermal expansion microspheres with smooth surface comprises the following steps:

[0027] S1: Mix unsaturated olefin monomer, crosslinking agent, modifier, initiator and foaming agent, stir evenly to form a mixed oil phase.

[0028] Specifically, the unsaturated olefin monomer accounts for 67-80wt% of the total oil phase, and the unsaturated olefin monomer includes monofunctional acrylate, which can be one or more of acrylonitrile, methacrylonitrile, methyl methacrylate, ethyl methacrylate, methyl acrylate, butyl acrylate, n-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, cyclohexyl acrylate, n-heptyl acrylate, 2-ethylhexyl acrylate, n-nonyl methacrylate, and isononyl acrylate. Preferably, the unsaturated olefin monomer is a combination of acrylonitrile, methyl methacrylate, and butyl acrylate, wherein the acrylonitrile accounts for 40-80wt% of the total oil phase, the methyl methacrylate accounts for 20-40wt% of the total oil phase, and the butyl acrylate accounts for 2-10wt% of the total oil phase. In this embodiment, the butyl acrylate is specifically n-butyl acrylate.

[0029] Specifically, the amount of the crosslinking agent accounts for 0.1 to 1.0 wt % of the total oil phase, and the crosslinking agent includes a multifunctional acrylate, which can be one or more of ethylene glycol dimethacrylate, ethylene glycol diacrylate, dipropylene glycol dimethacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, polyethylene glycol dimethacrylate, and polypropylene glycol dimethacrylate. Preferably, the crosslinking agent is ethylene glycol dimethacrylate, or trimethylolpropane triacrylate, or a combination of ethylene glycol dimethacrylate and trimethylolpropane triacrylate. In this embodiment, the crosslinking agent is ethylene glycol dimethacrylate.

[0030] Specifically, the amount of the modifier accounts for 0 to 1.0 wt % of the total oil phase. In specific applications, the heat-expandable microspheres modified by adding the modifier may have better dispersibility and wettability, thereby improving the stability of the foaming coating. Depending on the application scenario, the modifier may not be added in this method. In this embodiment, no modifier is added. The modifier includes a compound containing a carbon-carbon double bond. The compound containing a carbon-carbon double bond can specifically be one or more combinations of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, isobornyl acrylate, isobornyl methacrylate, vinyl silicon trimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmonomethoxysilane, vinyl silicon triethoxysilane, vinylmethyldiethoxysilane, and vinyldimethylmonoethoxysilane. Preferably, the modifier is selected from acrylic acid, methacrylic acid, or a combination of acrylic acid and methacrylic acid.

[0031] Specifically, the initiator usage ratio accounts for 0-1.0wt% of the total oil phase, and the initiator is specifically one or more of toluoyl peroxide, lauroyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, azobisisobutyronitrile, azobisisoheptanenitrile, azoisobutylcyanoformamide, di-sec-butyl peroxydicarbonate, and dibenzyl peroxydicarbonate. Preferably, the initiator is toluoyl peroxide, lauroyl peroxide, azobisisobutyronitrile, and azobisisoheptanenitrile. In this embodiment, the initiators selected are azobisisobutyronitrile and azobisisoheptanenitrile.

[0032] Specifically, the amount of the foaming agent accounts for 20-30wt% of the total oil phase, and the foaming agent is specifically one or more of n-butane, isobutane, n-pentane, isopentane, neopentane, cyclopentane, hexane, isohexane, octhexane, cyclohexane, heptane, isoheptane, octane and isooctane. Preferably, the foaming agent is isopentane.

[0033] S2: uniformly mix the nano-lignin aqueous dispersion, the emulsifier and the water phase inhibitor, and stir to form a mixed water phase;

[0034] Specifically, the proportion of the nano-lignin aqueous dispersion to the total aqueous phase is 90-100wt%. The nano-lignin aqueous dispersion is an aqueous dispersion of nanoparticles prepared from water-insoluble lignin. The water-insoluble lignin may be nano-alkali lignin, enzymatic lignin or sulfonate lignin. The solid content of the nano-alkali lignin is required to be in the range of 0.6-1.2wt%, and the particle size range is 10-500nm. In this embodiment, the nano-lignin aqueous dispersion uses nano-alkali lignin.

[0035] Specifically, the amount of the co-emulsifier accounts for 0 to 0.2 wt % of the total aqueous phase, and the co-emulsifier can be one or more of sodium lauryl sulfate, ammonium dodecylbenzenesulfonate, alkyl dimethyl sulfoethyl betaine, alkyl dimethyl sulfopropyl betaine, alkyl dimethyl hydroxypropyl phosphate betaine, polyvinyl alcohol, polyvinyl pyrrolidone, sodium alginate, gelatin, and methyl cellulose. Preferably, the co-emulsifier is sodium lauryl sulfate or polyvinyl pyrrolidone. In the present embodiment, the co-emulsifier is a combination of sodium lauryl sulfate and polyvinyl pyrrolidone.

[0036] Specifically, the proportion of the water phase inhibitor used accounts for 0-0.05wt% of the total water phase. The water phase inhibitor can be one or more of sodium nitrite, ferric nitrate, chromium nitrate, dichromate, tin chloride, ferric chloride, water-soluble ascorbic acid and its derivatives. In this embodiment, the water phase inhibitor is sodium nitrite. The specific components and amounts of the mixed oil phase and the mixed water phase in this embodiment can be seen in Table 1: "Proposal ratio and average particle size and surface morphology data table of thermal expansion microspheres".

[0037] S3: adding the mixed water phase obtained in step S2 to the mixed oil phase obtained in step S1, and homogenizing and emulsifying by a high-speed homogenizing emulsifier to form an emulsion. Generally, the emulsifying speed of the high-speed homogenizing emulsifier is 6000-14000 rpm.

[0038] S4: Add the emulsion obtained in step S3 to a reaction kettle, seal, pressurize, stir, and heat to react, and obtain a heat-expandable microsphere suspension. The specific parameters of the seal, pressurize, stir, and heat reaction are: pressure of 0.4-0.6 Mpa, stirring speed of 60-150 rpm, reaction temperature of 50-60°C, and reaction time of 15-20 hours.

[0039] S5: adding an alkaline washing liquid to the heat-expandable microsphere suspension obtained in step S4 to dissolve the nano-lignin on the surface of the heat-expandable microspheres, filtering, alkali washing and drying in sequence, and finally obtaining a heat-expandable microsphere powder with a smooth surface. Usually, the alkaline washing liquid is a sodium hydroxide aqueous solution with a concentration of 1 to 4 mol / L, or a potassium hydroxide aqueous solution with a concentration of 1 to 4 mol / L, or a mixture of sodium hydroxide and potassium hydroxide with a concentration of 1 to 4 mol / L. In this embodiment, the alkaline washing liquid is NaOH.

[0040] In Example 1, the specific implementation steps are as follows:

[0041] Step 1: Mix 48 g of acrylonitrile, 22.5 g of methyl methacrylate, 4.5 g of n-butyl acrylate, 0.3 g of ethylene glycol dimethacrylate, and 0.8 g of azobisisobutyronitrile, then add 25 g of isopentane and stir evenly to obtain a mixed oil phase.

[0042] Step 2: Mix and stir 300 g of a nano-lignin aqueous dispersion with a solid content of 1.2 wt% and an average particle size of 10-40 nm, 10 g of a polyvinyl pyrrolidone with a solid content of 5.0 wt%, 2.0 g of a sodium dodecyl sulfate aqueous solution with a solid content of 1.0 wt%, and 0.1 g of a sodium nitrite aqueous solution with a solid content of 10 wt% to form a mixed aqueous phase.

[0043] Step 3: Add the mixed water phase obtained in step 2 to the mixed oil phase obtained in step 1, and stir and emulsify rapidly at a rate of 6000 rpm to obtain a stable oil-in-water emulsion. Then seal the reactor, directly replace with nitrogen and pressurize to 0.40 MPa, maintain a stirring rate of 100 rpm, heat to 60°C and keep the reaction for 16 hours, then heat to 70°C and keep the reaction for 4 hours, cool to below 40°C, release the pressure and discharge the material, thereby obtaining a heat-expandable microsphere suspension.

[0044] Step 4: Add 1 mol / L NaOH aqueous solution to the heat-expandable microsphere suspension obtained in step 3, adjust the pH to between 8 and 9, then filter and dry to finally obtain heat-expandable microsphere powder.

[0045] In Examples 2 to 10, different from Example 1, the components of the oil phase preparation in step 1 and the water phase preparation in step 2 are adjusted, and the process parameters in step 3 are adjusted, and multiple experiments are performed to obtain different smooth heat-expandable microspheres. The specific parameters of Examples 2 to 10 can be seen in Table 1:

[0046] Table 1: Proportion of the solution and average particle size and surface morphology of thermal expansion microspheres

[0047]

[0048] As shown in Table 1: Scheme ratio and average particle size and surface morphology of heat-expandable microspheres, the emulsion formed by the nano-lignin emulsified oil phase in this method has high stability, and the experimental reaction can be successfully completed after the reaction. The particle size of the obtained heat-expandable microspheres shows a trend of decreasing as the emulsification speed increases, so the particle size of the heat-expandable microspheres can be more practically adjustable. The stirring speed, initiator and reaction temperature of the reaction process have an impact on the experimental residue after the reaction. The stirring rate is lower than 100rpm, and the residue increases because the low-speed stirring causes the microsphere polymerization process to receive less shear force, which makes it easier to react and agglomerate; the use of mixed initiators reduces the residue rate, and azobisisobutyronitrile can quickly form a shell at 60°C to protect the subsequent reaction agglomeration, but its dosage needs to be controlled. Excessive dosage will lead to too fast initiation rate and agglomeration, resulting in more residue.

[0049] Through the preparation method, thermal expansion microspheres with smooth surface can be obtained.

[0050] Comparative Example 1: Using a silicon dioxide emulsification system, the steps for preparing heat-expandable microspheres are as follows:

[0051] S101: 48 g of acrylonitrile, 22.5 g of methyl methacrylate, 4.5 g of n-butyl acrylate, 0.3 g of ethylene glycol dimethacrylate, and 0.6 g of lauroyl peroxide are mixed and stirred, and then 25 g of isopentane is added and stirred evenly to obtain a mixed oil phase.

[0052] S102: 300 g of silica sol with a solid content of 0.8 wt% and an average particle size of 10-20 nm, 10 g of polyvinyl pyrrolidone with a solid content of 5.0 wt%, 2.0 g of an aqueous solution of sodium dodecyl sulfate with a solid content of 1.0 wt%, and 0.1 g of an aqueous solution of sodium nitrite with a solid content of 10 wt%, adjusted to pH = 3.0, mixed and stirred to form a mixed aqueous phase.

[0053] S103: Add the mixed water phase obtained in step S102 to the mixed oil phase obtained in step S101, and stir and emulsify rapidly at a rate of 6000 rpm to obtain a stable oil-in-water emulsion. Then seal the reactor, directly replace with nitrogen and pressurize to 0.4 MPa, maintain a stirring rate of 100 rpm, heat to 70°C and keep the reaction for 16 hours, then heat to 80°C and keep the reaction for 4 hours, cool to below 40°C, release the pressure and discharge the material, thereby obtaining a heat-expandable microsphere suspension.

[0054] S104: adding 1 mol / L NaOH aqueous solution to the heat-expandable microsphere suspension obtained in step S103, adjusting the pH to between 8 and 9, then filtering and drying to finally obtain heat-expandable microsphere powder.

[0055] Comparative Example 2: The steps for preparing heat-expandable microspheres using a magnesium hydroxide emulsification system are as follows:

[0056] S201: 48 g of acrylonitrile, 22.5 g of methyl methacrylate, 4.5 g of n-butyl acrylate, 0.2 g of ethylene glycol dimethacrylate, and 0.6 g of lauroyl peroxide are mixed and stirred, and then 25 g of isopentane is added and stirred evenly to obtain a mixed oil phase.

[0057] S202: 150 g of NaOH dispersion with a solid content of 2.2 wt% and 150 g of NaOH dispersion with a solid content of 2.5 wt% are stirred and dispersed to form a Mg(OH)2 dispersion with a solid content of 0.8 wt%, and then 2.0 g of a sodium dodecyl sulfate aqueous solution with a solid content of 1.0 wt% and 0.1 g of a sodium nitrite aqueous solution with a solid content of 10 wt% are added to the Mg(OH)2 dispersion at one time, and the mixture is mixed and stirred to form a mixed aqueous phase.

[0058] S203: Add the mixed water phase obtained in step S202 to the mixed oil phase obtained in step S201, and stir and emulsify rapidly at a rate of 8000 rpm to obtain a stable oil-in-water emulsion. Then seal the reactor, directly replace with nitrogen and pressurize to 0.4 MPa, maintain a stirring rate of 100 rpm, heat to 70°C and keep the reaction for 16 hours, then heat to 80°C and keep the reaction for 4 hours, cool to below 40°C, release the pressure and discharge the material, thereby obtaining a heat-expandable microsphere suspension.

[0059] S204: adding 1 mol / L HCl aqueous solution to the heat-expandable microsphere suspension obtained in step S203, adjusting the pH to between 3 and 4, then filtering and drying to finally obtain heat-expandable microsphere powder.

[0060] The performance comparison parameters of the heat-expandable microspheres obtained in Example 1, Comparative Example 1 and Comparative Example 2 can be seen in Table 2:

[0061] Table 2: Comparison of thermal expansion microsphere performance

[0062]

[0063] Table 2: Comparison of the performance of heat-expandable microspheres. The morphology, pH and viscosity of the heat-expandable microspheres obtained by comparing Example 1, Comparative Example 1 and Comparative Example 2 are compared. Compared with Example 1 and Comparative Example 1 of the silica emulsified system, after alkali cleaning, the attached Figure 1 As shown in the figure, the surface of the heat-expandable microspheres obtained in Example 1 is smooth and the viscosity of the corresponding aqueous dispersion is also reduced, which is beneficial for subsequent applications requiring acidity and viscosity, such as the attached Figure 2 As shown, the surface of the heat-expandable microspheres obtained in Comparative Example 1 is rough. Compared with Example 1 and Comparative Example 2 of the magnesium hydroxide emulsified system, although the surfaces of the heat-expandable microspheres obtained in Example 1 and Comparative Example 2 are both smooth, the aqueous dispersion of the heat-expandable microspheres in Comparative Example 2 is alkaline, which is quite different from the present invention, and the application environment and system thereof will also be quite different, and both are applied to different working conditions.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing thermally expandable microspheres with a smooth surface, characterized in that: The following steps are involved: S1: Mix unsaturated olefin monomer, crosslinking agent, modifier, initiator and foaming agent, stir evenly to form a mixed oil phase; The unsaturated olefin monomer accounts for 67-80wt% of the total oil phase, the cross-linking agent accounts for 0.1-1.0wt% of the total oil phase, the modifier accounts for 0-1.0wt% of the total oil phase, the initiator accounts for 0-1.0wt% of the total oil phase, and the foaming agent accounts for 20-30wt% of the total oil phase; The unsaturated olefin monomer includes a monofunctional acrylate, and the monofunctional acrylate is one or more of acrylonitrile, methacrylonitrile, methyl methacrylate, ethyl methacrylate, methyl acrylate, butyl acrylate, n-butyl methacrylate, amyl methacrylate, isopentyl methacrylate, cyclohexyl acrylate, n-heptyl acrylate, 2-ethylhexyl acrylate, n-nonyl methacrylate, and isononyl acrylate; S2: uniformly mix the nano-lignin aqueous dispersion, the emulsifier and the water phase inhibitor, and stir to form a mixed water phase; The nano-lignin aqueous dispersion is a nano-particle aqueous dispersion prepared from water-insoluble lignin, and the water-insoluble lignin is nano-alkali lignin, enzymatic lignin or sulfonate lignin; The nano-lignin aqueous dispersion accounts for 90-100wt% of the total aqueous phase, the nano-alkali lignin solid content ranges from 0.6-1.2wt%, the particle size ranges from 10-500nm, the auxiliary emulsifier accounts for 0-0.2wt% of the total aqueous phase, and the aqueous phase inhibitor accounts for 0-0.05wt% of the total aqueous phase; S3: adding the mixed water phase obtained in step S2 to the mixed oil phase obtained in step S1, and homogenizing and emulsifying at high speed to form an emulsion; S4: adding the emulsion obtained in step S3 into a reaction kettle, sealing, pressurizing, stirring, and heating for reaction to obtain a heat-expandable microsphere suspension; S5: adding alkaline washing liquid to the heat-expandable microsphere suspension obtained in step S4 to dissolve the nano-lignin on the surface of the heat-expandable microspheres, filtering, alkali washing and drying in sequence, and finally obtaining heat-expandable microsphere powder with a smooth surface.

2. The method for preparing heat-expandable microspheres with smooth surface according to claim 1, characterized in that: The crosslinking agent includes a multifunctional acrylate, and the multifunctional acrylate is one or more of ethylene glycol dimethacrylate, ethylene glycol diacrylate, dipropylene glycol dimethacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, polyethylene glycol dimethacrylate, and polypropylene glycol dimethacrylate.

3. The method for preparing heat-expandable microspheres with smooth surface according to claim 1, characterized in that: The modifier includes a compound containing a carbon-carbon double bond, and the compound containing a carbon-carbon double bond is one or a combination of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, isobornyl acrylate, isobornyl methacrylate, vinyl silicon trimethoxy silane, vinyl methyl dimethoxy silane, vinyl dimethyl monomethoxy silane, vinyl silicon triethoxy silane, vinyl methyl diethoxy silane, and vinyl dimethyl monoethoxy silane.

4. The method for preparing heat-expandable microspheres with smooth surface according to claim 1, characterized in that: The initiator is one or more of toluoyl peroxide, lauroyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, azobisisobutyronitrile, azobisisoheptylnitrile, azoisobutylcyanamide, di-sec-butyl peroxydicarbonate, and dibenzyl peroxydicarbonate.

5. The method for preparing heat-expandable microspheres with smooth surface according to claim 1, characterized in that: The foaming agent is one or more of n-butane, isobutane, n-pentane, isopentane, neopentane, cyclopentane, hexane, isohexane, octhexane, cyclohexane, heptane, isoheptane, octane and isooctane.

6. The method for preparing heat-expandable microspheres with smooth surface according to claim 1, characterized in that: The auxiliary emulsifier is one or more of sodium dodecyl sulfate, ammonium dodecylbenzenesulfonate, alkyl dimethyl sulfoethyl betaine, alkyl dimethyl sulfopropyl betaine, alkyl dimethyl hydroxypropyl phosphate betaine, polyvinyl alcohol, polyvinyl pyrrolidone, sodium alginate, gelatin, and methyl cellulose; the water phase inhibitor is one or more of sodium nitrite, ferric nitrate, chromium nitrate, dichromate, tin chloride, ferric chloride, water-soluble ascorbic acid and its derivatives.

7. The method for preparing heat-expandable microspheres with smooth surface according to claim 1, characterized in that: The high-speed homogenization and emulsification speed in step S3 is 6000-14000 rpm, the specific parameters of the sealing pressurization, stirring and heating reaction in step S4 are: pressure of 0.4-0.6 MPa, stirring speed of 60-150 rpm, reaction temperature of 50-60° C., and insulation reaction time of 15-20 h, and the alkaline washing liquid in step S5 is a sodium hydroxide aqueous solution with a concentration of 1-4 mol / L, or a potassium hydroxide aqueous solution with a concentration of 1-4 mol / L, or a mixed solution of sodium hydroxide and potassium hydroxide with a concentration of 1-4 mol / L.

8. Thermal expansion microspheres with smooth surface, characterized in that: The compound is obtained by any one of the preparation methods of claims 1 to 7.